UJI EFEK DAUN KEMANGI (Ocimum basilicum L.) TERHADAP PENYEMBUHAN LUKA INSISI PADA KELINCI (Oryctolagus cuniculus) - Ramdani, Nurul Fitri; Mambo, Christi (Universitas Sam Ratulangi, 2014)
Abstract: Background and objectives : Medicinal plants have long been known and used in Indonesia, one of them being basil leaves (Ocimum basilicum L). Basil leaves contain flavonoid with anti-inflammatory properties that helps to reduce pain and swelling around wound. This study aimed to determine the effect of basil leaves on healing incision wound in rabbits. Methods: This current study is an experimental study using four rabbits as test animals. Three centimeters long and 0.3 cm deep incision wound were made on both the right side and the left side of the back. Incision wound on the right side of the back are treated with crushed basil leaves while the wounds on the left side of the back are left untreated, covered only with sterile gauze. Observations were carried out for two weeks with observe changes of the injuries in macroscopic length. Results: In the examination performed on the 14th day after incision were made, a reduction in wound size were observed. In the intervention wound, complete closure has not yet occurred, but the length of the wound is shorter and wound surface has started to blend with the surrounding tissues. Crusts are observed on the wound surface. In control wounds, a reduction in size is observed, with slight red coloration in the center of the wound. Conclusion: From the result of the study of effects of crussed basil leaves on the healing incision wound on rabbits, the length of the incision wound which were given crushed basil leaves reduced faster than the wounds which were left untreated.Keywords: Wound healing, incision wounds, basil leaves. Abstrak: Latar belakang dan tujuan : Bangsa Indonesia telah lama mengenal dan menggunakan tanaman berkhasiat obat, salah satu tumbuhan alam di Indonesia adalah daun kemangi (Ocimum basilicum L). Daun kemangi memiliki kandungan flavonoid bersifat anti inflamasi yang dapat mengurangi rasa sakit apabila terjadi pendarahan atau pembengkakan pada luka. Penelitian ini bertujuan untuk mengetahui efek pemberian daun kemangi terhadap penyembuhan luka insisi pada kelinci. Metode : Penelitian ini merupakan penelitian eksperimental dengan menggunakan empat ekor kelinci sebagai hewan uji. Punggung kanan dan kiri kelinci diinsisi sepanjang 3 cm dan kedalaman 0,3 cm. Luka pada punggung kanan diberi daun kemangi sedangkan luka pada punggung kiri tidak diberi perlakuan hanya ditutup dengan kasa steril. Pengamatan dilakukan selama dua minggu dengan melihat perubahan panjang luka secara makroskopik. Hasil : Pada hari ke-14, luka yang diberi daun kemangi menunjukkan luka mulai menutup belum sempurna, kerak masih menempel, panjang luka semakin pendek dan tampak permukaan luka sudah mulai menyatu dengan kulit sekitar. Pada luka yang tidak diberi daun kemangi terlihat sedikit mengecil namun luka masih berwarna merah di bagian tengah. Kesimpulan : Dari hasil penelitian uji efek daun kemangi terhadap penyembuhan luka insisi pada kelinci didapatkan bahwa panjang luka yang diberi daun kemangi lebih cepat mengecil dibandingkan dengan panjang luka yang tidak diberi daun kemangiKata Kunci : penyembuhan luka, luka insisi, daun kemangi.